Traditional Herbal Medicine Candidates as Complementary Treatments for COVID-19: A Review of Their Mechanisms, Pros and Cons. (10th October 2020) - Nugraha, Rhea Veda; Ridwansyah, Hastono; Ghozali, Mohammad; Khairani, Astrid Feinisa; Atik, Nur
Abstract : Coronavirus disease 2019 (COVID-19) is a new infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that belongs to the coronavirus family. The first case was reported in December 2019, and the disease has become a pandemic. Impaired immune regulation is one of the factors that play a role in its pathogenesis and results in poor outcomes of COVID-19 patients. There have been many studies with drug candidates used as antivirals or immunomodulators. However, the results of these investigations showed that the drug candidates were not significantly effective against the disease. Meanwhile, people believe that consuming herbal immunomodulators can prevent or even cure COVID-19. Unfortunately, specific preclinical and clinical trials to evaluate the effects of herbal immunoregulators have not been conducted. Certain natural compounds might be effective for the treatment of COVID-19 based on general concepts from previous experiments. This review discusses some herbal agents extracted from various plants, including Echinacea, Cinchona, Curcuma longa, and Curcuma xanthorrhiza, which are considered for the treatment of COVID-19. In addition, we discuss the pros and cons of utilising herbal medicine during the COVID-19 pandemic, draw some conclusions, and make recommendations at the end of the session.